Die Tragödie Europas - Möller, Horst; Cubar’jan, Aleksandr O. (2023)
The time between the Hitler-Stalin pact of 23 August 1939 and Germany`s invasion of the Soviet Union on 22 June 1941 remains a controversial period in European historiography. This volume presents the still multivalent interpretations of this first phase of World War II in German and Russian, as is the practice of the Historical Commission.